PENGARUH PENAMBAHAN KECOMBRANG TERHADAP KUALITAS BAKSO IKAN LELE SELAMA PENYIMPANAN - Zulni, Pelsi Zakia; Faridah, Anni; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The background of this study because of the lack of utilization of kecombrang asn a natural preservative for the manufacture of catfish meatball, in fact kecombrang it contains compounds an antimicrobial and antioxidants. This study aimed to analyze the effect of kecombrang as much as 0%, 2%, 3%, 4% and 5% of the quality of shape, color, aroma, texture and taste the catfish meatballs for storage. This study belongs to the kind of pure experiment with completely randomized design method. The date used are primary data. that has been obtained is then tabulated in the tables and analysis of variance (ANAVA), if different from the real continued by Duncan. The result show that there is a difference of influence for storage on the quality of the shape, color, aroma, texture and the catfish meatballs with the addition of kecombrang. Based on the organoleptik is known to the quality of the best is the addition of kecombrang 2%, while for as long as the storage of the best is the addition of kecombrang 5%.Keywords: Kecombrang, preservatives, catfish meatball, quality, storage.